2019
DOI: 10.3389/fneur.2019.00758
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia and Parkinson's Disease

Abstract: Parkinson's disease (PD) is a common debilitating neurodegenerative disease caused by a loss of dopamine neurons in the substantia nigra within the central nervous system (CNS). The process leading to this neuronal loss is poorly understood. Seborrheic dermatitis (SD) is a common benign inflammatory condition of the skin which mainly affects lipid-rich regions of the head and trunk. SD is caused by over proliferation of the lipophilic fungus Malassezia . PD and SD are strongly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 154 publications
(255 reference statements)
1
37
0
2
Order By: Relevance
“…These include those with Parkinson's disease (Skorvanek and Bhatia, 2017) patients as well as patients with spinal cord injury on which seborrheic dermatitis appears above the level of injury (Han et al, 2015), pointing toward brain-skin axis involvement. In the light of the recent implication of Malassezia yeasts in pancreatic ductal carcinoma development (Aykut et al, 2019), these epidemiological observations point to future research areas (Laurence et al, 2019). The understanding of the pathogenesis of seborrheic dermatitis is limited by the overlap with other conditions such as psoriasis (sebopsoriasis), the indistinct borders between seborrheic dermatitis and dandruff and the absence of a robust severity scoring system.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…These include those with Parkinson's disease (Skorvanek and Bhatia, 2017) patients as well as patients with spinal cord injury on which seborrheic dermatitis appears above the level of injury (Han et al, 2015), pointing toward brain-skin axis involvement. In the light of the recent implication of Malassezia yeasts in pancreatic ductal carcinoma development (Aykut et al, 2019), these epidemiological observations point to future research areas (Laurence et al, 2019). The understanding of the pathogenesis of seborrheic dermatitis is limited by the overlap with other conditions such as psoriasis (sebopsoriasis), the indistinct borders between seborrheic dermatitis and dandruff and the absence of a robust severity scoring system.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…In our meta-analysis, Malassezia infection was related to increased risk of PD (Laurence et al, 2019). Recent studies have shown that PD is associated with seborrheic dermatitis (Laurence et al, 2019), which is known to affect approximately 52%-59% PD patients, and is caused by the excessive proliferation of the lipophilic fungus Malassezia (Laurence et al, 2019). Interestingly, Malassezia has been identified in central nervous system, indicating a possibility that Malassezia may directly contribute to PD (Laurence et al, 2019).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Infection of various pathogenic microorganisms has been thought associated with increased risk of PD, including Helicobacter pylori (HP; Shen, Yang, Wu, Zhang, & Jiang, 2017), hepatitis C virus (HCV; Wijarnpreecha, Chesdachai, Jaruvongvanich, & Ungprasert, 2018), Malassezia (Laurence, Benito-León, & Calon, 2019), Chlamydophila pneumoniae (C. pneumonia; Bu et al, 2015), hepatitis B virus (HBV; Wijarnpreecha et al, 2018), influenza virus (Vlajinac et al, 2013), measles (Vlajinac et al, 2013), varicella-zoster virus (VZV; Hemling et al, 2003), mumps (Vlajinac et al, 2013), German measles (Vlajinac et al, 2013), pertussis (Vlajinac et al, 2013), scarlet fever (Vlajinac et al, 2013), rheumatic fever (Vlajinac et al, 2013), diphtheria (Vlajinac et al, 2013), cytomegalovirus (CMV; Bu et al, 2015), Epstein-Barr virus (EBV; Bu et al, 2015), herpes virus (HSV; Hemling et al, 2003), and Borrelia burgdorferi (B. burgdorferi; Bu et al, 2015). However, there are also studies indicated that infection of these pathogenic microorganisms may decrease or does not affect the risk of PD (Harris, Tsui, Marion, Shen, & Teschke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the possibility that some toxins or fungi can provoke PD has been suggested [30][31][32][33][34]. More recently, the possibility that Malassezia might be contributing to PD has been hypothesized [35]. However, the direct demonstration that these pathogens are present in brain tissue of PD patients was not provided.…”
Section: Ivyspringmentioning
confidence: 99%